2016
DOI: 10.1038/srep35712
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal state of intimal cells may explain higher propensity to ascending aortic aneurysm in bicuspid aortic valves

Abstract: Individuals with a bicuspid aortic valve (BAV) are at significantly higher risk of developing aortic complications than individuals with tricuspid aortic valves (TAV) and defective signaling during the embryonic development and/or life time exposure to abnormal hemodynamic have been proposed as underlying factors. However, an explanation for the molecular mechanisms of aortopathy in BAV has not yet been provided. We combined proteomics, RNA analyses, immunohistochemistry, and electron microscopy to identify mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 45 publications
7
38
0
Order By: Relevance
“…Previous studies have described features of the arterial proteome in murine 1-3 and cell models of atherosclerosis 4,5 and in limited numbers of human arterial samples with and without atherosclerosis [6][7][8][9][10][11][12][13][14][15][16][17][18] . To date there has not been a comprehensive survey of the human arterial proteome based on a large number of human coronary and aortic samples, using contemporary LC-MS/MS technology and subsequent identification of the proteins that signify presence of pre-clinical atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described features of the arterial proteome in murine 1-3 and cell models of atherosclerosis 4,5 and in limited numbers of human arterial samples with and without atherosclerosis [6][7][8][9][10][11][12][13][14][15][16][17][18] . To date there has not been a comprehensive survey of the human arterial proteome based on a large number of human coronary and aortic samples, using contemporary LC-MS/MS technology and subsequent identification of the proteins that signify presence of pre-clinical atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we provided cytological evidence for intimal instability and induction of EndMT-like process in non-dilated AscA of BAV patients due to downregulation and enhanced protein turnover of VE-Cadherin (CDH5) in addition to decreased expression of endothelial specific Claudin-5 (CLDN5). Moreover, mRNA expression of N-cadherin (CDH2) increased in dilated AscA of BAV patients compared to dilated AscA of TAV patients (16). Further, we showed that alteration in cadherin expression was accompanied by formation of pseudopodia and stress fibers in endothelium of non-dilated BAV, which is a second key hallmark of transition to a mesenchymal state.…”
Section: Endothelial Abnormality In Bav Patientsmentioning
confidence: 72%
“…We have previously performed comparative studies on BAV and TAV aortic intima-media specimen, from non-dilated or dilated aortas, to investigate differences at genomic, proteomic and epigenomic levels. First, by combining large-scale proteomic pathway analysis on differentially-expressed proteins in nondilated aortas, we showed enrichment of genes belonging to EMT, protein degradation and trafficking, cell junction dynamics, apoptosis, cell cycle and cancer-related biological processes (16). Second, to identify possible regulatory microRNAs (miRs) underlying the observed protein signature, we combined proteomic data with an in-silico network analysis approach (110).…”
Section: Non-physiological Shear Stress and Induction Of Endmt/emtmentioning
confidence: 99%
“…Aortic valve stenosis and regurgitation are associated with distinct alterations of the aortic wall [17]: we overcame this potential confounding factor by enrolling only patients similar in terms of valve dysfunction, i.e. with high-grade stenotic BAV/TAV, thus differentiating our study from others [18]. Similarly, we did not include all stages of aortopathy but selected patients with mild dilatation (diameter <45 mm), to obtain a homogeneous population of samples representative of the early phases of the disease.…”
Section: Discussionmentioning
confidence: 99%